Organization of Medical Assistance in Poland for Ukrainian Citizens During the Russia-Ukraine War - Fatyga, Edyta; Dzięgielewska-Gęsiak, Sylwia; Muc-Wierzgoń, Małgorzata (Frontiers in Public Health, 2022)
From February 24 2022 – March 29, 2022, Poland accepted 2 377 000 refugees fleeing Russia's invasion of Ukraine, mostly including women, children and the elderly. In this article, we present all activities and types of medical resources provided and organized in Poland for refugees from the first days of the conflict. Information was compiled from available data from the Polish Ministry of Health and other governmental and nongovernmental organizations, foundations and medical societies.